Anisotropic Conductive Film

By arranging conductive particles in repeating units with varying densities, the anisotropic conductive film effectively addresses the challenge of narrow pitch bumps, ensuring stable connections and reduced costs.

JP7607603B2Active Publication Date: 2024-12-27DEXERIALS CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022021048
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-05-05
Filing Date
2022-02-15
Publication Date
2024-12-27
Estimated Expiration
2037-04-24

AI Technical Summary

Technical Problem

Existing anisotropic conductive films face challenges in accommodating narrow pitch bumps while maintaining low conductive particle density to prevent short circuits and reduce manufacturing costs.

Method used

The conductive particles are arranged in repeating units with varying numbers of particles in parallel, forming dense and sparse areas across the film surface, ensuring stable connection and reduced particle density.

Benefits of technology

This arrangement stabilizes the connection quality by reducing the required thrust force and minimizing short circuits, thereby lowering manufacturing costs and improving the reliability of electronic component connections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607603000005
    Figure 0007607603000005
  • Figure 0007607603000006
    Figure 0007607603000006
  • Figure 0007607603000007
    Figure 0007607603000007
Patent Text Reader

Abstract

It is possible to accommodate narrow-pitch bumps and reduce the number density of conductive particles. The present invention provides an anisotropic conductive film that can [Solution] An anisotropic conductive film 1A in which conductive particles 2 are arranged in an insulating resin binder 3, The conductive particles 2 are arranged in a line at intervals, and the number of conductive particles is 2p, 2q, and 2r. Repeating units 5 of conductive particles, each consisting of different particles arranged in parallel, are formed on the entire surface of the anisotropic conductive film. They are arranged repeatedly throughout the book.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anisotropic conductive film. [Background technology]

[0002] Anisotropic conductive films, which have conductive particles dispersed in an insulating resin binder, are widely used when mounting electronic components such as IC chips on wiring boards, etc. With the trend toward narrower bump pitches accompanying the high-density mounting of electronic components, there is a strong demand for anisotropic conductive films that can enhance the capture of conductive particles in the bumps and prevent short circuits between adjacent bumps.

[0003] In response to such demands, it has been proposed to arrange the conductive particles in an anisotropic conductive film in a lattice pattern, with the arrangement axis tilted relative to the longitudinal direction of the anisotropic conductive film, and in this case to space the conductive particles apart at a predetermined distance (Patent Document 1 and Patent Document 2).It has also been proposed to link the conductive particles together to form locally dense regions, thereby enabling narrower pitches to be achieved (Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 4887700 [Patent Document 2] Japanese Patent Application Publication No. 9-320345 [Patent Document 3] Special Publication No. 2002-519473 Summary of the Invention [Problem to be solved by the invention]

[0005] As described in Patent Documents 1 and 2, when conductive particles are arranged in a simple lattice pattern, the bump layout is determined by the inclination angle of the array axis and the distance between conductive particles. Therefore, when the bumps have a narrow pitch, the distance between conductive particles must be narrowed, making it difficult to avoid short circuits. In addition, the number density of conductive particles increases, and the manufacturing cost of the anisotropic conductive film also increases.

[0006] On the other hand, if the distance between the conductive particles is not narrowed, there is a concern that a sufficient number of conductive particles will not be captured by the terminal.

[0007] In addition, the technique of forming locally dense regions of conductive particles by linking conductive particles is not preferred because it increases the risk of short circuits when multiple linked conductive particles simultaneously enter the space between bumps.

[0008] Therefore, an object of the present invention is to provide an anisotropic conductive film that can accommodate narrow-pitch bumps and has a lower conductive particle density than conventional anisotropic conductive films. [Means for solving the problem]

[0009] The inventor discovered that by repeatedly arranging units of conductive particles, in which the conductive particles are spaced apart and arranged in a specific manner, over the entire surface of an anisotropic conductive film, it is possible to form regions of sparsely populated conductive particles over the entire surface of the film, thereby making it possible to connect bumps with a narrow pitch in the dense regions of the sparsely populated regions, and since the conductive particles are spaced apart even in the dense regions, the risk of shorting is reduced, and furthermore the presence of the sparse regions makes it possible to reduce the number density of conductive particles throughout the film, and thus arrived at the present invention.

[0010] That is, the present invention provides an anisotropic conductive film having conductive particles disposed in an insulating resin binder, To provide an anisotropic conductive film in which a repeating unit of conductive particles, each of which is a conductive particle row in which conductive particles are aligned in a line at intervals and different numbers of conductive particles are arranged in parallel, is repeatedly arranged. Effect of the Invention

[0011] According to the anisotropic conductive film of the present invention, since the individual conductive particles are not arranged in a simple lattice pattern, but are repeatedly arranged in a repeating unit of conductive particles with a specific particle arrangement, it is possible to form a dense and sparse region of conductive particles in the film, and therefore it is possible to suppress an increase in the number density of conductive particles in the entire anisotropic conductive film. Therefore, it is possible to suppress an increase in manufacturing costs associated with an increase in the number density of conductive particles. In addition, generally, when the number density of conductive particles increases, the thrust force required for the pressing tool during anisotropic conductive connection also increases. However, according to the anisotropic conductive film of the present invention, the increase in the number density of conductive particles is suppressed, and therefore the increase in the thrust force required for the pressing tool during anisotropic conductive connection is also suppressed, so that it is possible to prevent electronic components from being deformed by anisotropic conductive connection. In addition, since excessive thrust force is not required for the pressing tool, the thrust force of the pressing tool is stabilized, and the quality of the anisotropically conductively connected electronic components is stabilized.

[0012] On the other hand, in the anisotropic conductive film of the present invention, repeat units each having a dense area of ​​conductive particles are repeatedly formed vertically and horizontally, which enables connection of bumps with a narrow pitch. Furthermore, since the conductive particles are spaced apart within the repeat unit, it is possible to avoid short circuits even if the repeat unit straddles the space between terminals. [Brief description of the drawings]

[0013] [Figure 1A] FIG. 1A is a plan view showing the arrangement of conductive particles in an anisotropic conductive film 1A according to an embodiment of the present invention. [Figure 1B] FIG. 1B is a cross-sectional view of an anisotropic conductive film 1A according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a plan view of an anisotropic conductive film 1B according to the embodiment. [Diagram 3] FIG. 3 is a plan view of an anisotropic conductive film 1C according to the embodiment. [Figure 4] FIG. 4 is a plan view of an anisotropic conductive film 1D according to an embodiment of the present invention. [Diagram 5] FIG. 5 is a plan view of an anisotropic conductive film 1E according to the embodiment. [Figure 6] FIG. 6 is a plan view of an anisotropic conductive film 1F according to the embodiment. [Figure 7] FIG. 7 is a plan view of an anisotropic conductive film 1G according to the embodiment. [Figure 8] FIG. 8 is a plan view of an anisotropic conductive film 1H according to the embodiment. [Figure 9] FIG. 9 is a plan view of an anisotropic conductive film 1I according to the embodiment. [Figure 10] FIG. 10 is a plan view of an anisotropic conductive film 1J according to the embodiment. [Figure 11] FIG. 11 is a plan view of an anisotropic conductive film 1K according to the embodiment. [Figure 12] FIG. 12 is a cross-sectional view of an anisotropic conductive film 1a according to the embodiment. [Figure 13] FIG. 13 is a cross-sectional view of an anisotropic conductive film 1b according to the embodiment. [Figure 14] FIG. 14 is a cross-sectional view of an anisotropic conductive film 1c according to the embodiment. [Figure 15] FIG. 15 is a cross-sectional view of an anisotropic conductive film 1d according to an embodiment of the present invention. [Figure 16] FIG. 16 is a cross-sectional view of an anisotropic conductive film 1e according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The anisotropic conductive film of the present invention will now be described in detail with reference to the drawings, in which the same reference numerals denote the same or equivalent components.

[0015] <Overall structure of anisotropic conductive film> FIG. 1A is a plan view showing the arrangement of conductive particles in an anisotropic conductive film 1A according to one embodiment of the present invention, and FIG. 1B is a cross-sectional view thereof. This anisotropic conductive film 1A has a structure in which conductive particles 2 are arranged in a single layer on or near the surface of an insulating resin binder 3, and an insulating adhesive layer 4 is laminated thereon.

[0016] The anisotropic conductive film of the present invention may have a configuration in which the insulating adhesive layer 4 is omitted and the conductive particles 2 are embedded in the insulating resin binder 3 .

[0017] <Conductive particles> The conductive particles 2 may be appropriately selected from those used in known anisotropic conductive films. Examples include metal particles such as nickel, copper, silver, gold, and palladium, and metal-coated resin particles in which the surface of resin particles such as polyamide and polybenzoguanamine is coated with a metal such as nickel. The size of the conductive particles to be arranged is preferably 1 to 30 μm, more preferably 1 μm or more and 10 μm or less, and even more preferably 2 μm or more and 6 μm or less.

[0018] The average particle size of the conductive particles 2 can be measured by an image type or laser type particle size distribution meter. The anisotropic conductive film may be observed in a plan view and the particle size may be measured. In this case, preferably 200 or more particles, more preferably 500 or more particles, and even more preferably 1000 or more particles are measured.

[0019] The surfaces of the conductive particles 2 are preferably covered with an insulating coat or insulating particle treatment. Such a coating is easily peeled off from the surfaces of the conductive particles 2 and does not interfere with anisotropic connection. Furthermore, protrusions may be provided on the entire surface or part of the surface of the conductive particles 2. The height of the protrusions is preferably within 20% of the conductive particle diameter, and more preferably within 10%.

[0020] <Arrangement of conductive particles> (Repeat unit) The arrangement of the conductive particles 2 in the anisotropic conductive film 1A in a planar view is such that a repeat unit 5, in which conductive particle rows 2p, 2q, and 2r and a single conductive particle 2s are juxtaposed, is repeated vertically and horizontally (X direction, Y direction) over the entire surface of the anisotropic conductive film 1A, and the polygon formed by sequentially connecting the centers of the conductive particles that form the outline of the repeat unit 5 is a triangle. Note that the anisotropic conductive film of the present invention can have areas in which no conductive particles are arranged, if necessary.

[0021] In each of the conductive particle rows 2p, 2q, and 2r, the conductive particles 2 are arranged in a straight line with a space therebetween in a plan view. The number of conductive particles constituting the conductive particle rows 2p, 2q, and 2r is gradually different, and the conductive particle rows 2p, 2q, and 2r are arranged in parallel. By repeating the particle arrangement in which the conductive particle rows 2p, 2q, and 2r with gradually different particle numbers are arranged in parallel, the number density of the conductive particles is locally sparse and dense, so that even if there is a slight positional deviation when the anisotropic conductive film is attached to an electronic component, it becomes easier to capture a stable number of conductive particles in each bump constituting the bump row. This is more effective when anisotropic conductive connections are made continuously. That is, when a simple lattice arrangement is used and the attachment of the anisotropic conductive film to an electronic component is slightly misaligned, the number of captured particles is likely to vary depending on the presence or absence and the degree of the positional deviation, especially at the bump end. In order to suppress this variation, it has been proposed to tilt the angle of the lattice arrangement with respect to the longitudinal direction of the film (Patent Document 1, etc.). However, when the bump width or the distance between the bumps becomes narrower, the effect of inclining the lattice arrangement is limited. In contrast, in the present invention, the conductive particles are captured at any point in the range of the bump length by varying the number density of the conductive particles within the range of the bump length. In other words, a single bump simultaneously generates positions where the conductive particles are captured and positions where they are not captured. As a result, if the shape (area) of the bump is similar in any of the bump arrangements, the number of conductive particles captured by the bump can be stabilized by appropriately setting the repeat interval of the repeat unit. Therefore, even if a minute positional deviation occurs in the attachment of the anisotropic conductive film, and also when the connection bodies are continuously manufactured on a production line, the capture state of the conductive particles in the bump arrangement for each connection body tends to be stable. In addition, by simultaneously generating positions where the conductive particles are captured and positions where they are not captured in one bump, it is expected that the inspection labor after the anisotropic conductive connection will be reduced and quality control will be improved. For example, by simultaneously generating positions in which conductive particles are captured and positions in which they are not captured in a single bump, it becomes easier to compare successively obtained connections during indentation inspection after anisotropic conductive connection.In addition, since the presence or absence of misalignment when the anisotropic conductive film is temporarily attached to the electronic components in the anisotropic conductive connection process can be compared between connected bodies manufactured in succession, it is expected that it will become easier to determine areas that need improvement in the connection device.

[0022] The arrangement of the conductive particles 2 in the repeat unit 5 is such that a part of the conductive particles 2 constituting the repeat unit 5 occupies a part of the vertices of each of the 6 regular regular hexagons when the regular hexagons are arranged without gaps. Alternatively, the conductive particles constituting the repeat unit 5 are arranged so that the vertices of the regular triangles when the regular triangles are arranged without gaps overlap with the conductive particles constituting the repeat unit 5. In other words, the repeat unit 5 is an arrangement in which conductive particles are present at each lattice point of the hexagonal lattice arrangement, and the conductive particles at predetermined lattice points are regularly removed. In this way, when the conductive particles 2 are arranged at the lattice points of the hexagonal lattice arrangement, the particle arrangement of the repeat unit 5 is easily recognized, and the design is facilitated. Note that, as described later, the arrangement of the conductive particles in the repeat unit is not limited to that based on a hexagonal lattice, but may be based on a square lattice, or may be based on an arrangement in which regular polygons of octagons or more are arranged vertically and horizontally and the sides of adjacent regular polygons are overlapped.

[0023] (Repeating pattern of repeating units) More specifically, in the X direction, the repeat unit 5 in the anisotropic conductive film 1A shown in FIG. 1A is repeated with particle intervals in the repeat unit 5. In addition, in the Y direction, the repeat unit 5B, which is obtained by inverting the repeat unit 5 about the symmetric axis in the Y direction, and the repeat unit 5 are alternately repeated with intervals. In this case, it is preferable that the position of the longitudinal side of the anisotropic conductive film when the polygon formed by sequentially connecting the centers of the conductive particles forming the outline of the repeat unit is projected in the short direction of the anisotropic conductive film partially overlaps with the similar position of the repeat unit adjacent to the repeat unit. In general, the width direction of the terminal of the electronic component is the long direction of the anisotropic conductive film, and therefore, when the polygon forming the outline of the repeat unit is overlapped as described above, the probability that the conductive particles are captured by the terminal of the electronic component is increased. In addition, the longitudinal direction and the short direction of the anisotropic conductive film may be interchanged. This is because there are cases where it is better to interchange depending on the terminal layout.

[0024] In addition, when considering the repeating unit of the conductive particle 2, a unit consisting of the repeating unit 5 and its inverted repeating unit 5B can also be seen as the repeating unit of the conductive particle. However, in the present invention, the repeating unit is preferably a unit consisting of multiple parallel rows of conductive particles, and is the smallest unit repeated vertically and horizontally.

[0025] (Repeat unit size) The size of the anisotropic conductive film of the repeating unit 5 and the distance between the repeating units are preferably determined based on the bump width and the space between the bumps of the electronic components to be connected with the anisotropic conductive film 1A.

[0026] For example, when the connection objects are not fine pitched, the size of the repeat unit 5 in the longitudinal direction of the anisotropic conductive film is preferably smaller than either the bump width or the space between the bumps, whichever is narrower. Even with such a size, the repeat units 5 are repeatedly arranged, so that the minimum number of conductive particles required for connection can be captured by the bumps, and the number of conductive particles not involved in the connection can be reduced, thereby reducing the cost of the anisotropic conductive film. In addition, by making the sides of the polygon that forms the outline of the repeat unit 5 oblique to the short direction of the anisotropic conductive film 1A, stable connection performance can be obtained regardless of the cutting position of the long anisotropic conductive film.

[0027] When the connection objects are not fine pitch, the distance between adjacent repeat units 5, 5B in the longitudinal direction of the anisotropic conductive film is preferably shorter than the space between the bumps of the electronic components connected by the anisotropic conductive film.

[0028] On the other hand, when the connection objects have a fine pitch, it is preferable that the size of the repeating units 5, 5B in the longitudinal direction of the anisotropic conductive film is set to a size that can span the space between the bumps.

[0029] As an example of the boundary between fine pitch and non-fine pitch, a bump width of less than 30 μm can be considered fine pitch, and a bump width of 30 μm or more can be considered non-fine pitch.

[0030] As described above, when determining the size of the repeat unit 5 depending on the connection target, the number of conductive particles constituting the repeat unit 5 is preferably 5 or more, more preferably 10 or more, and even more preferably 20 or more. In general, it is preferable that 3 or more, particularly 10 or more conductive particles are captured between opposing terminals connected by anisotropic conductive connection, so that when the repeat unit is sandwiched between opposing terminals, it can be confirmed from the indentation of one repeat unit that such a number of conductive particles are captured.

[0031] (Specific deformation forms of repeating units) In the present invention, the arrangement of the conductive particles 2 in the repeating unit 5 and the vertical and horizontal repeating pitch of the repeating unit 5 can be appropriately changed according to the shape of the terminals to be connected in the anisotropic conductive connection and the pitch of the terminals. Therefore, compared to a case where the conductive particles 2 are arranged in a simple lattice pattern, a high capturing ability can be achieved with a smaller number of conductive particles in the anisotropic conductive film as a whole.

[0032] For example, in addition to the repeating form shown in Fig. 1A, repeating units 5 may be repeated in a staggered arrangement, as in an anisotropic conductive film 1B shown in Fig. 2. In a staggered arrangement, the effect of resin flow on conductive particles during anisotropic conductive connection of electronic components differs between bumps located in the center of the staggered arrangement and bumps located on the outside, and the risk of short circuits also differs between bumps located in the center of the staggered arrangement and bumps located on the outside, so the shape of repeating unit 5 can be appropriately changed to adjust the flow of resin flow.

[0033] The arrangement of the conductive particles 2 in the repeat unit 5 can also be changed as appropriate according to the shape of the terminal to be connected in the anisotropic conductive connection and the pitch of the terminal. For example, as in the anisotropic conductive film 1C shown in FIG. 3, the number of conductive particles constituting the conductive particle row 2p in one repeat unit 5 may be gradually increased or decreased, or a single conductive particle 2s may be repeatedly arranged along with the repetition of the repeat unit 5. Furthermore, in three parallel conductive particle rows in one repeat unit, the number of conductive particles constituting the central conductive particle row may be greater or smaller than the number of conductive particles constituting the conductive particle rows on both sides. For example, as in the anisotropic conductive film 1D shown in FIG. 4, in each repeat unit 5, the conductive particle row 2p in which four conductive particles 2 are arranged in the longitudinal direction of the anisotropic conductive film, the conductive particle row 2q in which two conductive particles are arranged, the conductive particle row 2r in which three conductive particles are arranged, and one conductive particle 2s are arranged in parallel. When the number of conductive particles in the parallel conductive particle row in one repeat unit is increased or decreased, the outer shape of the repeat unit becomes a complex polygonal shape, which makes it easier to connect to a radial bump array (so-called fan-out bump). The arrangement of conductive particles in one repeat unit is expressed by the number of conductive particles in the conductive particle row constituting the repeat unit. For example, when the repeat unit shown in FIG. 4 is expressed as [4-2-3-1], examples of modified examples of this repeat unit include [4-1-4-1], [4-3-1-2], [3-2-2-1], [4-1-2-3], and [4-2-1-3]. These may be combined and repeatedly arranged. For example, [4-2-3-1-2-1-4-3] may be mentioned.

[0034] In addition, the distance between conductive particles in one conductive particle row may be the same or different between the conductive particle rows arranged in parallel in one repeat unit. For example, as in the anisotropic conductive film 1E shown in FIG. 5, the outer shape of the repeat unit 5 may be a rhombus, and the conductive particle 2 may be arranged in the center. In this repeat unit, a conductive particle row 2m consisting of five conductive particles, a conductive particle row 2n consisting of two conductive particles, a conductive particle row 2o consisting of three conductive particles, a conductive particle row 2p consisting of two conductive particles, and a conductive particle row 2q consisting of five conductive particles are arranged in parallel, and the distance between conductive particles in the conductive particle rows 2m and 2q, the distance between conductive particles in the conductive particle rows 2n and 2p, and the distance between conductive particles in the conductive particle row 2o are different from each other. If this is expressed as [4-3-2-1] in the above notation, the arrangement may be one in which the central conductive particle 3 is omitted. This is because the risk of short circuit occurrence can be further reduced.

[0035] In the above-mentioned anisotropic conductive films 1A, 1B, 1C, 1D, and 1E, the arrangement of the conductive particles 2 in the repeating units 5 and 5B exists at the lattice points of a hexagonal lattice, but as long as the conductive particle rows 2p are parallel, they may be arranged based on a square lattice as in the anisotropic conductive film 1F shown in Figure 6.

[0036] 7 is obtained by repeatedly arranging, over the entire surface of the film, a repeat unit 5 consisting of two rows of conductive particles 2p and 2q, and a repeat unit 5B in which the array axis of the conductive particles in the repeat unit 5 is rotated by 60°. In this manner, a certain repeat unit and a repeat unit obtained by rotating the same by a predetermined angle may be used in combination.

[0037] The shape of the repeat unit may be a regular polygon formed by sequentially connecting the conductive particles that form the outline of the repeat unit. This is preferable because it makes it easier to recognize the arrangement of the conductive particles. In this case, each conductive particle that forms the repeat unit does not need to be present at the lattice points of a hexagonal lattice or a square lattice. For example, the outline of the repeat unit 5 can be formed into a regular octagon as in the anisotropic conductive film 1H shown in FIG. 8. In this case, the conductive particles that form the outline of the repeat unit are arranged at the vertices of a regular octagon in a lattice in which the sides of adjacent regular octagons are overlapped, as shown by the dashed lines in the figure. Similarly, the conductive particles may be arranged at the vertices of a regular dodecagon or a regular polygon having more than one side. In addition, a repeat unit having an outline of an approximately regular polygon having more than one side may be formed by arranging conductive particles at the lattice points of a hexagonal lattice or a square lattice. For example, the repeating unit 5 of the anisotropic conductive film 1I shown in Fig. 9 is formed from conductive particles 2 arranged on the lattice points of a square lattice, and is an octagon that is symmetrical in both the longitudinal and lateral directions of the anisotropic conductive film, making it easy to recognize the arrangement of the conductive particles.

[0038] In addition, the parallel conductive particle rows in the repeat unit do not necessarily have to be parallel to each other, and may be arranged radially. For example, as in the anisotropic conductive film 1J shown in Fig. 10, repeat units 5 having radially arranged conductive particle rows 2m, 2n, 2o, 2p, and 2q can be repeatedly arranged vertically and horizontally. In this case, the conductive particles 2 do not have to be present at the lattice points of a hexagonal lattice or a square lattice.

[0039] (Direction of the repeat unit edges) 1A, each side of a triangle 5x formed by sequentially connecting the centers of conductive particles forming the outline of a repeating unit 5 is oblique to the longitudinal or lateral direction of the anisotropic conductive film 1A. As a result, a tangent line L1 of a conductive particle 2a in the longitudinal direction of the anisotropic conductive film penetrates a conductive particle 2b adjacent to the conductive particle 2a in the longitudinal direction of the anisotropic conductive film. Also, a tangent line L2 of a conductive particle 2a in the lateral direction of the anisotropic conductive film penetrates a conductive particle 2c adjacent to the conductive particle 2a in the lateral direction of the anisotropic conductive film. Generally, during anisotropic conductive connection, the longitudinal direction of the anisotropic conductive film becomes the transverse direction of the bump. Therefore, if the sides of the polygon 5x of the repeating unit 5 are oblique to the longitudinal or transverse direction of the anisotropic conductive film 1A, it is possible to prevent multiple conductive particles from lining up in a straight line along the edge of the bump. This makes it possible to avoid the phenomenon in which multiple conductive particles arranged in a straight line come off the terminal together and no longer contribute to conductivity, thereby improving the capture ability of the conductive particles 2.

[0040] In addition, when the longitudinal direction of the anisotropic conductive film becomes the transverse direction of the bump during anisotropic conductive connection, the polygon 5x formed by the conductive particles that form the outline of the repeating unit 5 does not necessarily have to have all of its sides oblique to the longitudinal or transverse direction of the anisotropic conductive film; however, from the viewpoint of the capture of the conductive particles, it is preferable that preferably two or more sides, and more preferably three or more sides, are oblique to the longitudinal or transverse direction of the anisotropic conductive film.

[0041] On the other hand, when the bump arrangement pattern is radial (so-called fan-out bump), it is preferable that the polygon forming the repeat unit has a side in the longitudinal or transverse direction of the anisotropic conductive film. That is, in order to prevent the bumps to be connected from being misaligned due to thermal expansion of the base material on which the bumps are provided, the bump arrangement pattern may be radial (for example, JP 2007-19550 A, JP 2015-232660 A, etc.), in which case the angle between the longitudinal direction of each bump and the longitudinal direction of the anisotropic conductive film gradually changes. Therefore, even if the side of the polygon of the repeat unit 5 is not oblique to the longitudinal or transverse direction of the anisotropic conductive film, the side of the polygon of the repeat unit 5 and 5B obliquely intersects with the edge in the longitudinal direction of each radially arranged bump. Therefore, it is possible to avoid the phenomenon that many of the conductive particles that are caught on the edge of the bump during anisotropic conductive connection are not captured by the bump, and the capture ability of the conductive particles is reduced. On the other hand, the radial arrangement pattern of the bumps is usually formed symmetrically. Therefore, in order to easily check the quality of the connection state by the indentation after anisotropic conductive connection, it is preferable that the polygon forming the outline of the repeat unit 5 has a side in the longitudinal direction or the lateral direction of the anisotropic conductive film. Therefore, for example, when the repeat unit is a triangle similar to the anisotropic conductive film 1A shown in FIG. 1A, it is preferable to arrange the repeat unit 5 so that one side 5a of the triangle forming the outline of the repeat unit 5 is parallel to the longitudinal direction or the lateral direction of the anisotropic conductive film as in the anisotropic conductive film 1K shown in FIG. 11. In addition, as in the repeat unit 5 of the anisotropic conductive film 1H shown in FIG. 8, it may have a side 5a parallel to the longitudinal direction of the anisotropic conductive film and a side 5b parallel to the lateral direction.

[0042] The arrangement of the conductive particles in the present invention is not limited to the arrangement of the repeating units shown in the figures. For example, the arrangement shown in the figures may be inclined. In this case, the arrangement may be inclined by 90 degrees, that is, the longitudinal direction and the transverse direction of the film may be interchanged. In addition, the interval between the repeating units 5 or the interval between the conductive particles in the repeating units may be changed.

[0043] <Distance between nearest conductive particles> The closest interparticle distance of the conductive particles is preferably 0.5 times or more the average conductive particle diameter, both between adjacent conductive particles within a repeat unit 5 and between adjacent conductive particles between repeat units 5. The distance between repeat units 5 is preferably longer than the distance between adjacent conductive particles within a repeat unit 5. If this distance is too short, short circuits are likely to occur due to contact between the conductive particles. The upper limit of the distance between adjacent conductive particles is determined according to the bump shape and bump pitch. For example, in the case of a bump width of 200 μm and a space between bumps of 200 μm, when at least one conductive particle is present in either the bump width or the space between bumps, the distance between conductive particles is less than 400 μm. In order to ensure the capture of the conductive particles, it is preferable to make it less than 200 μm.

[0044] <Conductive particle number density> The number density of the conductive particles is set to 50,000 particles / mm when the average particle diameter of the conductive particles is less than 10 μm, in order to suppress the manufacturing cost of the anisotropic conductive film and to prevent the thrust force required for the pressing jig used for anisotropic conductive connection from becoming excessively large. 2 Less than 35,000 pieces / mm is preferable. 2 Less than 30,000 pieces / mm is more preferable. 2 On the other hand, if the number density of the conductive particles is too low, the conductive particles may not be sufficiently captured by the terminals, which may cause a conduction failure. Therefore, the number density of the conductive particles is preferably 300 particles / mm or less. 2 More than 500 pieces / mm is preferable. 2 More preferably, 800 pieces / mm 2 The above is even more preferable.

[0045] In addition, when the average particle size of the conductive particles is 10 μm or more, the number of particles is 15 / mm 2 More than 50 pieces / mm is preferable. 2 More preferably, 160 pieces / mm 2 The above is even more preferable. If the conductive particle diameter is larger, the occupied area ratio of the conductive particles also increases. For the same reason, 1800 particles / mm 2Less than 1100 pieces / mm is preferable. 2 Less than 800 pieces / mm is more preferable. 2 The following is even more preferred: The number density of the conductive particles may be locally (for example, within an area of ​​200 μm×200 μm) outside the above-mentioned range.

[0046] <Insulating resin binder> As the insulating resin binder 3, a thermally polymerizable composition, a photopolymerizable composition, a photothermally polymerizable composition, etc., which are used as insulating resin binders in known anisotropic conductive films, can be appropriately selected and used. Among these, examples of the thermally polymerizable composition include a thermally radically polymerizable resin composition containing an acrylate compound and a thermal radical polymerization initiator, a thermally cationic polymerizable resin composition containing an epoxy compound and a thermal cationic polymerization initiator, and a thermally anionic polymerizable resin composition containing an epoxy compound and a thermal anionic polymerization initiator, and examples of the photopolymerizable composition include a photoradical polymerizable resin composition containing an acrylate compound and a photoradical polymerization initiator. If no particular problem occurs, multiple types of polymerizable compositions may be used in combination. Examples of combinations include a combination of a thermally cationic polymerizable composition and a thermally radical polymerizable composition.

[0047] Here, the photopolymerization initiator may contain multiple types of light that react to different wavelengths, which allows different wavelengths to be used for photocuring the resin constituting the insulating resin layer and for photocuring the resin for bonding electronic components together during anisotropic connection during the manufacture of the anisotropic conductive film.

[0048] When the insulating resin binder 3 is formed using a photopolymerizable composition, all or part of the photopolymerizable compound contained in the insulating resin binder 3 can be photocured by photocuring during the manufacture of the anisotropic conductive film. This photocuring maintains or fixes the arrangement of the conductive particles 2 in the insulating resin binder 3, and is expected to suppress short circuits and improve capture. In addition, by adjusting the photocuring conditions, the viscosity of the insulating resin layer in the manufacturing process of the anisotropic conductive film can be adjusted.

[0049] The amount of the photopolymerizable compound in the insulating resin binder 3 is preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably less than 2% by mass, because if the amount of the photopolymerizable compound is too much, the thrust force applied during the anisotropic conductive connection increases.

[0050] On the other hand, the thermally polymerizable composition contains a thermally polymerizable compound and a thermal polymerization initiator, and the thermally polymerizable compound may also function as a photopolymerizable compound. The thermally polymerizable composition may contain a photopolymerizable compound and a photopolymerization initiator in addition to the thermally polymerizable compound. Preferably, the thermally polymerizable composition contains a photopolymerizable compound and a photopolymerization initiator in addition to the thermally polymerizable compound. For example, a thermal cationic polymerization initiator is used as the thermal polymerization initiator, an epoxy resin is used as the thermally polymerizable compound, a photoradical initiator is used as the photopolymerization initiator, and an acrylate compound is used as the photopolymerizable compound. The insulating resin binder 3 may contain a cured product of these polymerizable compositions.

[0051] The acrylate compound used as the thermally or photopolymerizable compound may be a conventionally known thermally polymerizable (meth)acrylate monomer, such as a monofunctional (meth)acrylate monomer or a polyfunctional (meth)acrylate monomer having two or more functional groups.

[0052] In addition, the epoxy compound used as the polymerizable compound forms a three-dimensional network structure and imparts good heat resistance and adhesiveness, and it is preferable to use a solid epoxy resin and a liquid epoxy resin in combination. Here, the solid epoxy resin means an epoxy resin that is solid at room temperature. In addition, the liquid epoxy resin means an epoxy resin that is liquid at room temperature. In addition, room temperature means a temperature range of 5 to 35°C as specified by JIS Z 8703. In the present invention, two or more kinds of epoxy compounds can be used in combination. In addition to the epoxy compound, an oxetane compound may be used in combination.

[0053] The solid epoxy resin is not particularly limited as long as it is compatible with the liquid epoxy resin and is solid at room temperature, and examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, multifunctional type epoxy resin, dicyclopentadiene type epoxy resin, novolac phenol type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, etc., and one of these can be used alone or two or more can be used in combination. Among these, it is preferable to use bisphenol A type epoxy resin.

[0054] The liquid epoxy resin is not particularly limited as long as it is liquid at room temperature, and examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac phenol type epoxy resin, naphthalene type epoxy resin, etc., and one of these may be used alone or two or more may be used in combination. In particular, it is preferable to use bisphenol A type epoxy resin from the viewpoint of tackiness, flexibility, etc. of the film.

[0055] Among the thermal polymerization initiators, examples of the thermal radical polymerization initiator include organic peroxides, azo compounds, etc. In particular, organic peroxides that do not generate nitrogen, which causes bubbles, can be preferably used.

[0056] If the amount of the thermal radical polymerization initiator used is too small, curing will be insufficient, and if it is too large, the product life will be shortened, so the amount is preferably 2 to 60 parts by mass, more preferably 5 to 40 parts by mass, per 100 parts by mass of the (meth)acrylate compound.

[0057] As the thermal cationic polymerization initiator, any known thermal cationic polymerization initiator for epoxy compounds can be used. For example, iodonium salts, sulfonium salts, phosphonium salts, ferrocenes, and the like that generate acids by heat can be used. In particular, aromatic sulfonium salts that show good latency with respect to temperature can be preferably used.

[0058] The amount of the thermal cationic polymerization initiator used is preferably 2 to 60 parts by mass, more preferably 5 to 40 parts by mass, relative to 100 parts by mass of the epoxy compound, since too little will tend to result in poor curing, and too much will tend to shorten the product life.

[0059] As the thermal anionic polymerization initiator, a known one that is usually used can be used. For example, organic acid dihydrazide, dicyandiamide, amine compound, polyamide amine compound, cyanate ester compound, phenol resin, acid anhydride, carboxylic acid, tertiary amine compound, imidazole, Lewis acid, Bronsted acid salt, polymercaptan-based hardener, urea resin, melamine resin, isocyanate compound, blocked isocyanate compound, etc. can be mentioned, and one kind from these can be used alone or two or more kinds can be used in combination. Among these, it is preferable to use a microcapsule-type latent hardener that has an imidazole modified body as a core and its surface is covered with polyurethane.

[0060] It is preferable that the thermally polymerizable composition contains a film-forming resin. The film-forming resin corresponds to a high molecular weight resin having an average molecular weight of, for example, 10,000 or more, and from the viewpoint of film formability, the average molecular weight is preferably about 10,000 to 80,000. Examples of the film-forming resin include various resins such as phenoxy resin, polyester resin, polyurethane resin, polyester urethane resin, acrylic resin, polyimide resin, and butyral resin, which may be used alone or in combination of two or more kinds. Among these, it is preferable to suitably use phenoxy resin from the viewpoint of film formation state, connection reliability, etc.

[0061] The thermally polymerizable composition may contain an insulating filler to adjust the melt viscosity. Examples of such a filler include silica powder and alumina powder. The size of the insulating filler is preferably 20 to 1000 nm, and the amount of the insulating filler is preferably 5 to 50 parts by mass per 100 parts by mass of the thermally polymerizable compound (photopolymerizable compound) such as an epoxy compound.

[0062] Furthermore, the insulating material may contain a filler different from the insulating filler, a softener, an accelerator, an antioxidant, a colorant (pigment, dye), an organic solvent, an ion catcher, and the like.

[0063] If necessary, a stress relaxation agent, a silane coupling agent, an inorganic filler, etc. may be blended. Examples of the stress relaxation agent include hydrogenated styrene-butadiene block copolymers and hydrogenated styrene-isoprene block copolymers. Examples of the silane coupling agent include epoxy-based, methacryloxy-based, amino-based, vinyl-based, mercapto-sulfide-based, and ureido-based agents. Examples of the inorganic filler include silica, talc, titanium oxide, calcium carbonate, and magnesium oxide.

[0064] The insulating resin binder 3 can be formed by forming a film of a coating composition containing the above-mentioned resin by a coating method, drying it, further curing it, or by forming it into a film by a known method in advance. The insulating resin binder 3 may be obtained by laminating resin layers as necessary. In addition, the insulating resin binder 3 is preferably formed on a release film such as a polyethylene terephthalate film that has been subjected to a release treatment.

[0065] (Viscosity of insulating resin binder) The minimum melt viscosity of the insulating resin binder 3 can be appropriately determined according to the manufacturing method of the anisotropic conductive film. For example, when the manufacturing method of the anisotropic conductive film is a method in which conductive particles are held in a predetermined arrangement on the surface of the insulating resin binder and the conductive particles are pressed into the insulating resin binder, the minimum melt viscosity of the resin is preferably 1100 Pa·s or more in order to enable the insulating resin binder to be formed into a film. In addition, as described later, in order to form a recess 3b around the exposed portion of the conductive particle 2 pressed into the insulating resin binder 3 as shown in FIG. 12 or FIG. 13, or to form a recess 3c directly above the conductive particle 2 pressed into the insulating resin binder 3 as shown in FIG. 14, the minimum melt viscosity is preferably 1500 Pa·s or more, more preferably 2000 Pa·s or more, even more preferably 3000 to 15000 Pa·s, and particularly 3000 to 10000 Pa·s. This minimum melt viscosity can be determined, for example, by using a rotational rheometer (manufactured by TA Instruments) at a heating rate of 10°C / min, a constant measurement pressure of 5 g, and a measurement plate with a diameter of 8 mm. When the step of pressing the conductive particles 2 into the insulating resin binder 3 is performed at preferably 40 to 80°C, more preferably 50 to 60°C, from the viewpoint of forming the recesses 3b or 3c as described above, the lower limit of the viscosity at 60°C is preferably 3000 Pa·s or more, more preferably 4000 Pa·s or more, and even more preferably 4500 Pa·s or more, and the upper limit is preferably 20000 Pa·s or less, more preferably 15000 Pa·s or less, and even more preferably 10000 Pa·s or less.

[0066] By making the viscosity of the resin that constitutes the insulating resin binder 3 high as described above, when the anisotropic conductive film is used, the conductive particles 2 in the anisotropic conductive film can be prevented from being carried away by the flow of the molten insulating resin binder 3 when the conductive particles 2 are sandwiched between opposing connection objects such as electronic components and heated and pressurized.

[0067] (Thickness of insulating resin binder) The thickness La of the insulating resin binder 3 is preferably 1 μm or more and 60 μm or less, more preferably 1 μm or more and 30 μm or less, and even more preferably 2 μm or more and 15 μm or less. In addition, in terms of the relationship between the thickness La of the insulating resin binder 3 and the average particle diameter D of the conductive particles 2, the ratio (La / D) thereof is preferably 0.6 to 10. If the thickness La of the insulating resin binder 3 is too large, the conductive particles are likely to be displaced during anisotropic conductive connection, and the capture ability of the conductive particles in the terminal decreases. This tendency is remarkable when La / D exceeds 10. Therefore, La / D is more preferably 8 or less, and even more preferably 6 or less. On the other hand, if the thickness La of the insulating resin binder 3 is too small and La / D is less than 0.6, it becomes difficult for the insulating resin binder 3 to maintain the conductive particles in a predetermined particle dispersion state or a predetermined arrangement. In particular, when the terminal to be connected is a high density COG, the ratio (La / D) of the layer thickness La of the insulating resin binder 3 to the particle diameter D of the conductive particles 2 is preferably 0.8-2.

[0068] (Embedding mode of conductive particles in insulating resin binder) There is no particular restriction on the embedding state of the conductive particles 2 in the insulating resin binder 3, but when the anisotropic conductive film is sandwiched between opposing components and heated and pressurized to perform an anisotropic conductive connection, it is preferable that the conductive particles 2 are partially exposed from the insulating resin binder 3, and a recess 3b is formed around the exposed part of the conductive particle 2 with respect to the tangent plane 3P of the surface 3a of the insulating resin binder in the center between adjacent conductive particles 2, as shown in Figures 12 and 13, or that a recess 3c is formed with respect to the tangent plane 3P similar to the above in the insulating resin binder part directly above the conductive particle 2 pressed into the insulating resin binder 3, as shown in Figure 14, so that there is an undulation on the surface of the insulating resin binder 3 directly above the conductive particle 2. The conductive particles 2 are flattened when they are sandwiched between the electrodes of opposing electronic components and heated and pressurized, but the presence of the recess 3b shown in Figures 12 and 13 reduces the resistance that the conductive particles 2 receive from the insulating resin binder 3 compared to the case where the recess 3b is not present. This makes it easier for the conductive particles 2 to be sandwiched between the opposing electrodes, improving the conductive performance. Also, among the resins constituting the insulating resin binder 3, recesses 3c (FIG. 14) are formed on the surface of the resin directly above the conductive particles 2, so that the pressure during heating and pressurization is more likely to concentrate on the conductive particles 2 than in the absence of recesses 3c, making it easier for the conductive particles 2 to be sandwiched between the electrodes, improving the conductive performance.

[0069] In order to easily obtain the effects of the above-mentioned recesses 3b and 3c, the ratio (Le / D) of the maximum depth Le of the recess 3b (FIGS. 12 and 13) around the exposed portion of the conductive particle 2 to the average particle diameter D of the conductive particle 2 is preferably less than 50%, more preferably less than 30%, and even more preferably 20 to 25%. The ratio (Ld / D) of the maximum diameter Ld of the recess 3b (FIGS. 12 and 13) around the exposed portion of the conductive particle 2 to the average particle diameter D of the conductive particle 2 is preferably 100% or more, more preferably 100 to 150%. The ratio (Lf / D) of the maximum depth Lf of the recess 3c (FIG. 14) in the resin directly above the conductive particle 2 to the average particle diameter D of the conductive particle 2 is preferably greater than 0, and preferably less than 10%, and more preferably less than 5%.

[0070] The diameter Lc of the exposed portion of the conductive particle 2 can be equal to or smaller than the average particle diameter D of the conductive particle 2, and is preferably 10 to 90% of the average particle diameter D. The exposed portion may be at one point on the top 2t of the conductive particle 2, or the conductive particle 2 may be completely buried in the insulating resin binder 3, so that the diameter Lc is zero.

[0071] (Position of conductive particles in the thickness direction of the insulating resin binder) In order to easily obtain the effect of the above-mentioned recess 3b, it is preferable that the ratio (Lb / D) (hereinafter referred to as the embedding rate) of the distance Lb (hereinafter referred to as the embedding amount) from the deepest part of the conductive particle 2 from the tangent plane 3p of the surface 3a of the insulating resin binder at the center between adjacent conductive particles 2 to the average particle diameter D of the conductive particle 2 is 60% or more and 105% or less.

[0072] <Insulating adhesive layer> In the anisotropic conductive film of the present invention, an insulating adhesive layer 4 having a different viscosity or adhesion from the resin constituting the insulating resin binder 3 may be laminated on the insulating resin binder 3 in which the conductive particles 2 are arranged.

[0073] When the insulating resin binder 3 has the above-mentioned recess 3b formed therein, the insulating adhesive layer 4 may be laminated on the surface of the insulating resin binder 3 on which the recess 3b is formed, as in the anisotropic conductive film 1d shown in FIG. 15, or on the surface opposite to the surface on which the recess 3b is formed, as in the anisotropic conductive film 1e shown in FIG. 16. The same applies when the insulating resin binder 3 has a recess 3c formed therein. By laminating the insulating adhesive layer 4, when an electronic component is anisotropically conductively connected using the anisotropic conductive film, the space formed by the electrodes and bumps of the electronic component can be filled, improving adhesion.

[0074] In addition, when the insulating adhesive layer 4 is laminated on the insulating resin binder 3, it is preferable that the insulating adhesive layer 4 is on the side of the first electronic component such as an IC chip (in other words, the insulating resin binder 3 is on the side of the second electronic component such as a substrate) regardless of whether the insulating adhesive layer 4 is on the surface on which the recesses 3b and 3c are formed. In this way, it is possible to avoid unintended movement of the conductive particles and improve the capture property. Note that, usually, the first electronic component such as an IC chip is the pressing jig side, and the second electronic component such as a substrate is the stage side, and the anisotropic conductive film is temporarily bonded to the second electronic component, and then the first electronic component and the second electronic component are permanently bonded. However, depending on the size of the thermocompression region of the second electronic component, the anisotropic conductive film is temporarily attached to the first electronic component, and then the first electronic component and the second electronic component are permanently bonded.

[0075] As the insulating adhesive layer 4, any insulating adhesive layer used in a known anisotropic conductive film can be appropriately selected and used. The insulating adhesive layer 4 may be one in which the viscosity is adjusted to be lower using the same resin as the insulating resin binder 3 described above. The greater the difference between the minimum melt viscosities of the insulating adhesive layer 4 and the insulating resin binder 3, the easier it is for the insulating adhesive layer 4 to fill the space formed by the electrodes and bumps of the electronic components, and the effect of improving the adhesion between the electronic components can be expected. In addition, the greater the difference, the smaller the amount of movement of the resin constituting the insulating resin binder 3 during anisotropic conductive connection, and the easier it is to improve the capture of conductive particles in the terminals. In practical use, the minimum melt viscosity ratio between the insulating adhesive layer 4 and the insulating resin binder 3 is preferably 2 or more, more preferably 5 or more, and even more preferably 8 or more. On the other hand, if this ratio is too large, there is a risk of resin overflow or blocking occurring when a long anisotropic conductive film is wound, so in practical use, it is preferable that it is 15 or less. More specifically, the preferred minimum melt viscosity of the insulating adhesive layer 4 satisfies the above ratio and is 3000 Pa·s or less, more preferably 2000 Pa·s or less, and particularly 100 to 2000 Pa·s.

[0076] The insulating adhesive layer 4 can be formed by forming a film of a coating composition containing the same resin as that forming the insulating resin binder 3 by a coating method, drying it, and further hardening it, or by forming it into a film by a known method.

[0077] The thickness of the insulating adhesive layer 4 is preferably 1 μm or more and 30 μm or less, and more preferably 2 μm or more and 15 μm or less.

[0078] Furthermore, the minimum melt viscosity of the entire anisotropic conductive film, which is the combination of the insulating resin binder 3 and the insulating adhesive layer 4, depends on the ratio of the thicknesses of the insulating resin binder 3 and the insulating adhesive layer 4, but for practical purposes it may be 8000 Pa·s or less, and in order to facilitate filling between the bumps, it may be 200 to 7000 Pa·s, and is preferably 200 to 4000 Pa·s.

[0079] Insulating fillers such as silica fine particles, alumina, and aluminum hydroxide may be added to the insulating resin binder 3 and the insulating adhesive layer 4 as necessary. The amount of insulating filler is preferably 3 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the resin constituting those layers. This makes it possible to suppress unnecessary movement of conductive particles in the molten resin even if the anisotropic conductive film melts during anisotropic conductive connection.

[0080] <Method of manufacturing anisotropic conductive film> The anisotropic conductive film can be manufactured, for example, by manufacturing a transfer mold for arranging conductive particles in a predetermined array, filling the recesses of the transfer mold with conductive particles, covering the mold with insulating resin binder 3 formed on a release film, and applying pressure to push the conductive particles 2 into the insulating resin binder 3, thereby transferring the conductive particles 2 to the insulating resin binder 3. Alternatively, an insulating adhesive layer 4 is further laminated on the conductive particles 2. In this manner, an anisotropic conductive film 1A can be obtained.

[0081] Alternatively, the conductive particles may be filled in the recesses of the transfer mold, and then the insulating resin binder may be placed thereon, the conductive particles may be transferred from the transfer mold to the surface of the insulating resin binder, and the conductive particles on the insulating resin binder may be pressed into the insulating resin binder to produce an anisotropic conductive film. The amount of conductive particles embedded (Lb) can be adjusted by the pressing force, temperature, etc. during the pressing. The shape and depth of the recesses 3b and 3c can be adjusted by the viscosity of the insulating resin binder during pressing, the pressing speed, temperature, etc. For example, the lower limit of the viscosity of the insulating resin binder during pressing the conductive particles is preferably 3000 Pa·s or more, more preferably 4000 Pa·s or more, and even more preferably 4500 Pa·s or more, and the upper limit is preferably 20000 Pa·s or less, more preferably 15000 Pa·s or less, and even more preferably 10000 Pa·s or less. Such a viscosity is preferably obtained at 40 to 80°C, more preferably 50 to 60°C. More specifically, when manufacturing an anisotropic conductive film 1a having the depressions 3b shown in Figure 12 on the surface of the insulating resin binder, the viscosity of the insulating resin binder when the conductive particles are pressed in can be 8000 Pa·s (50 to 60°C), and when manufacturing an anisotropic conductive film 1c having the depressions 3c shown in Figure 14, the viscosity of the insulating resin binder when the conductive particles are pressed in can be 4500 Pa·s (50 to 60°C).

[0082] As the transfer mold, in addition to filling the recesses with conductive particles, a mold having a slight adhesive applied to the top surfaces of the protrusions so that the conductive particles adhere to the top surfaces may be used.

[0083] These transfer molds can be manufactured by using or adapting known techniques such as machining, photolithography, printing, and the like.

[0084] As a method for arranging the conductive particles in a predetermined array, a method using a biaxially stretched film or the like may be used instead of the method using a transfer mold.

[0085] <Wrapped body> The anisotropic conductive film is preferably wound on a reel in order to be continuously used for connecting electronic components. The length of the film roll may be 5 m or more, and is preferably 10 m or more. There is no particular upper limit, but from the viewpoint of handling of shipped goods, it is preferably 5000 m or less, more preferably 1000 m or less, and even more preferably 500 m or less.

[0086] The film roll may be made by connecting anisotropic conductive films shorter than the entire length with a connecting tape. The connecting points may be multiple, regular, or random. There is no particular limit to the thickness of the connecting tape as long as it does not impair performance, but if it is too thick, it may affect resin overflow and blocking, so it is preferably 10 to 40 μm. There is also no particular limit to the width of the film, but an example is 0.5 to 5 mm.

[0087] The film wrap allows for continuous anisotropic conductive connections, which can contribute to reducing the cost of the connections.

[0088] <Connection structure> The anisotropic conductive film of the present invention can be preferably used when a first electronic component such as an FPC, an IC chip, or an IC module is anisotropically conductively connected to a second electronic component such as an FPC, a rigid substrate, a ceramic substrate, a glass substrate, or a plastic substrate by heat or light. In addition, IC chips or IC modules can be stacked to anisotropically conductively connect the first electronic components to each other. The connection structure thus obtained and the method for producing the same are also part of the present invention.

[0089] A preferred method for connecting electronic components using an anisotropic conductive film is to temporarily attach the interface of the anisotropic conductive film on the side where conductive particles are present in the thickness direction to a second electronic component such as a wiring board placed on a stage, mount a first electronic component such as an IC chip on the temporarily attached anisotropic conductive film, and perform thermocompression bonding from the first electronic component side using a pressing tool, in order to enhance connection reliability. Similar electronic component connections can also be performed using photocuring.

[0090] In addition, when it is difficult to temporarily attach the anisotropic conductive film to the second electronic component such as a wiring board due to the size of the connection area of ​​the second electronic component such as a wiring board, the anisotropic conductive film is temporarily attached to the first electronic component of an IC chip placed on a stage, and then the first electronic component and the second electronic component are thermocompression bonded. EXAMPLES

[0091] Experimental Examples 1 to 8 (Preparation of anisotropic conductive film) Regarding the anisotropic conductive film used for COG connection, the effects of the resin composition of the insulating resin binder and the arrangement of conductive particles on the film forming ability and conductive characteristics were investigated as follows.

[0092] First, the resin compositions forming the insulating resin binder and the insulating adhesive layer were prepared with the formulations shown in Table 1. In this case, the minimum melt viscosity of the resin composition was adjusted according to the preparation conditions of the insulating resin composition. The resin composition forming the insulating resin binder was applied to a PET film having a film thickness of 50 μm with a bar coater, and dried in an oven at 80° C. for 5 minutes to form an insulating resin binder layer having a thickness La shown in Table 2 on the PET film. In the same manner, an insulating adhesive layer was formed on the PET film with a thickness shown in Table 2.

[0093] [Table 1]

[0094] Next, a mold was prepared so that the conductive particles were arranged in a plan view as shown in Table 2, and the center-to-center distance between the nearest conductive particles in the repeating unit was 6 μm. Pellets of a known transparent resin were poured in a molten state into the mold, and cooled and solidified to form a resin mold with recesses arranged as shown in Table 2. Here, in Experimental Example 8, the conductive particles were arranged in a hexagonal lattice (number density 32,000 particles / mm 2 ) with one of the lattice axes tilted at 15° with respect to the longitudinal direction of the anisotropic conductive film.

[0095] Metal-coated resin particles (Sekisui Chemical Co., Ltd., AUL703, average particle diameter 3 μm) were prepared as conductive particles, and the conductive particles were filled into the recesses of the resin mold, and the above-mentioned insulating resin binder was placed on top of the conductive particles, and the conductive particles were attached by pressing at 60°C and 0.5 MPa. The insulating resin binder was then peeled off from the mold, and the conductive particles on the insulating resin binder were pressed into the insulating resin binder by pressing (pressing conditions: 60 to 70°C, 0.5 MPa), to produce a film in which the conductive particles were embedded in the insulating resin binder in the state shown in Table 2. In this case, the embedding state of the conductive particles was controlled by the pressing conditions. As a result, in Experimental Example 4, the film shape was not maintained after the conductive particles were pressed, but in the other Experimental Examples, a film in which the conductive particles were embedded could be produced. Observation with a metallurgical microscope showed that dents were observed around the exposed parts of the embedded conductive particles or directly above the embedded conductive particles, as shown in Table 2. In each experimental example except for experimental example 4, both dents around the exposed parts of the conductive particles and dents directly in front of the conductive particles were observed, and Table 4 shows the measured values ​​for each experimental example where the dents were most clearly observed.

[0096] An anisotropic conductive film with two resin layers was produced by laminating an insulating adhesive layer on the side of the film with the conductive particles embedded in it where the conductive particles were pressed in. However, in Experimental Example 4, the film shape was not maintained after the conductive particles were pressed in, so no further evaluation was performed.

[0097] (evaluation) For each anisotropic conductive film of the experimental examples, (a) the initial conduction resistance and (b) the conduction reliability were measured as follows. The results are shown in Table 2.

[0098] (a) Initial conduction resistance The anisotropic conductive film of each experimental example was sandwiched between the glass substrate on the stage and the IC for evaluating the electrical conductivity characteristics on the pressing tool side, and heated and pressurized with the pressing tool (180°C, 5 seconds) to obtain each connection for evaluation. In this case, the thrust force of the pressing tool was changed to three levels: low (40 MPa), medium (60 MPa), and high (80 MPa), to obtain three types of connections for evaluation.

[0099] Here, the terminal patterns of the conduction characteristic evaluation IC and the glass substrate correspond to each other, and their sizes are as follows: When connecting the evaluation IC and the glass substrate, the longitudinal direction of the anisotropic conductive film was aligned with the transverse direction of the bump.

[0100] Conduction characteristic evaluation IC External size 1.8×20.0mm Thickness 0.5mm Bump specifications: Size 30 x 85 μm, distance between bumps 50 μm, bump height 15 μm

[0101] Glass substrate (ITO wiring) Glass material: Corning 1737F External size 30×50mm Thickness 0.5mm Electrode ITO wiring

[0102] The initial conduction resistance of the resulting connection for evaluation was measured and rated according to the following three-level evaluation criteria. Evaluation criteria for initial conduction resistance (in practice, there is no problem if it is less than 2Ω) A: Less than 0.4Ω B: 0.4Ω or more and less than 0.8Ω C: 0.8Ω or more

[0103] (b) Conduction reliability A reliability test was performed on the evaluation connection product prepared in (a) by placing it in a thermostatic chamber at a temperature of 85°C and a humidity of 85% RH for 500 hours. The conduction resistance thereafter was measured in the same manner as the initial conduction resistance, and was evaluated according to the following three-level evaluation criteria.

[0104] Evaluation criteria for continuity reliability (in practice, there is no problem if it is less than 5 Ω) A: Less than 1.2Ω B: 1.2Ω or more and less than 2Ω C: 2Ω or more

[0105] [Table 2]

[0106] From Table 2, it can be seen that in Experimental Example 4, where the minimum melt viscosity of the insulating resin binder is 800 Pa·s, it is difficult to form a film with depressions in the insulating resin binder near the conductive particles. On the other hand, in Experimental Examples where the minimum melt viscosity of the insulating resin binder is 1500 Pa·s or more, it is possible to form convex portions in the insulating resin binder near the conductive particles by adjusting the conditions when embedding the conductive particles, and the anisotropic conductive film thus obtained has good conductive properties for COG. It can also be seen that in Experimental Examples 1 to 7, where the conductive particle number density is lower than in Experimental Example 8, which has a hexagonal lattice arrangement, anisotropic conductive connection can be performed at a lower pressure.

[0107] (c) Short Rate Using the anisotropic conductive films of experimental examples 1 to 3 and 5 to 8, evaluation connections were obtained under connection conditions of 180°C, 60 MPa, and 5 seconds using the following short circuit rate evaluation IC, and the number of short circuits in the obtained evaluation connections was counted. The short circuit rate was calculated as the ratio of the measured number of short circuits to the number of terminals of the evaluation IC.

[0108] IC for evaluating short rate (7.5μm spaced comb-tooth TEG (test element group): External size 15×13mm Thickness: 0.5mm Bump specifications: Size 25 x 140 μm, distance between bumps 7.5 μm, bump height 15 μm

[0109] A short circuit level of less than 50 ppm is practically preferable, and the anisotropic conductive films of Experimental Examples 1 to 3 and 5 to 8 all had a level of less than 50 ppm.

[0110] In addition, when the number of conductive particles trapped per bump was measured for each of the experimental examples except for experimental example 4, 10 or more conductive particles were found to be trapped in each of the experimental examples.

[0111] Experimental Examples 9-16 (Preparation of anisotropic conductive film) Regarding the anisotropic conductive film used for FOG connection, the effects of the resin composition of the insulating resin binder and the arrangement of conductive particles on the film forming ability and conductive characteristics were investigated as follows.

[0112] That is, a resin composition forming an insulating resin binder and an insulating adhesive layer was prepared according to the formulation shown in Table 3, and an anisotropic conductive film was produced using these in the same manner as in Experimental Example 1. The arrangement of the conductive particles and the center-to-center distance of the nearest particles in this case are shown in Table 4. In Experimental Example 16, the conductive particles were arranged in a hexagonal lattice arrangement (number density 15,000 particles / mm 2 ) with one of the lattice axes tilted at 15° with respect to the longitudinal direction of the anisotropic conductive film.

[0113] In the process of producing this anisotropic conductive film, after the conductive particles were pressed into the insulating resin binder, the film shape was not maintained in Experimental Example 12, but the film shape was maintained in the other experimental examples. Therefore, the embedding state of the conductive particles was observed and measured with a metallurgical microscope for the anisotropic conductive films of the experimental examples except for Experimental Example 12, and further evaluation was performed. The embedding state of the conductive particles in each experimental example is shown in Table 4. As with Table 2, the embedding state shown in Table 4 is the measurement value where the depression in the insulating resin binder was most clearly observed for each experimental example.

[0114] (evaluation) For each anisotropic conductive film of the experimental examples, (a) the initial conduction resistance and (b) the conduction reliability were measured as follows. The results are shown in Table 4.

[0115] (a) Initial conduction resistance The anisotropic conductive film obtained in each experimental example was cut to 2 mm x 40 mm, sandwiched between an FPC for evaluating conductive characteristics and a glass substrate, and heated and pressed (180°C, 5 seconds) with a tool width of 2 mm to obtain each connection for evaluation. In this case, the thrust force of the pressing tool was changed to three levels: low (3 MPa), medium (4.5 MPa), and high (6 MPa), to obtain three types of connection for evaluation. The conductive resistance of the obtained connection for evaluation was measured in the same manner as in experimental example 1, and the measured values ​​were evaluated into three levels according to the following criteria.

[0116] Evaluation FPC: Terminal pitch: 20μm Terminal width / Terminal space 8.5μm / 11.5μm Polyimide film thickness (PI) / copper foil thickness (Cu)=38 / 8, Sn plating

[0117] Non-alkali glass substrate: Electrode ITO wiring Thickness 0.7mm

[0118] Evaluation criteria for initial conduction resistance A: Less than 1.6 Ω B: 1.6Ω or more and less than 2.0Ω C: 2.0Ω or more

[0119] (b) Conduction reliability The connection for evaluation prepared in (a) was placed in a thermostatic chamber at a temperature of 85°C and a humidity of 85% RH for 500 hours, and the electrical resistance thereafter was measured in the same manner as the initial electrical resistance, and the measured values ​​were evaluated into three levels according to the following criteria.

[0120] Conduction reliability evaluation criteria A: Less than 3.0 Ω B: 3.0Ω or more and less than 4Ω C: 4.0Ω or more

[0121] Table 4 shows that in Experimental Example 12, where the minimum melt viscosity of the insulating resin binder was 800 Pa s, it was difficult to form a film with dents. On the other hand, in Experimental Examples where the minimum melt viscosity of the insulating resin layer was 1500 Pa s or more, it was found that dents could be formed near the conductive particles in the insulating resin binder by adjusting the conditions when embedding the conductive particles, and that the anisotropic conductive film thus obtained had good conductive properties for FOG use.

[0122] (c) Short Rate The number of short circuits in the evaluation connections whose initial conduction resistance was measured was counted, and the short circuit occurrence rate was calculated from the measured number of short circuits and the number of gaps in the evaluation connections. If the short circuit occurrence rate is less than 100 ppm, there is no problem in practical use. In all of Experimental Examples 9 to 11 and 13 to 16, the incidence of short circuits was less than 100 ppm.

[0123] In addition, when the number of conductive particles trapped per bump was measured for each of the experimental examples except for experimental example 12, 10 or more conductive particles were found to be trapped in each of the experimental examples.

[0124] [Table 3]

[0125] [Table 4] [Explanation of symbols]

[0126] 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1a, 1b, 1c, 1d, 1e Anisotropic Conductive Film 2, 2a, 2b, 2c, 2s conductive particles 2m, 2n, 2o, 2p, 2q, 2r conductive particle array 2t Top of conductive particle 3. Insulating resin binder 3a Surface of insulating resin binder 3b, 3c dent 3P tangent plane 4. Insulating adhesive layer 5, 5B repeat unit 5a Side parallel to the longitudinal direction of the anisotropic conductive film 5b Side parallel to the short direction of the anisotropic conductive film 5x A polygon formed by connecting the centers of the conductive particles that form the outline of the repeating unit D Average particle size L1, L2 external tangent line La Thickness of insulating resin binder Lb Amount of conductive particles embedded Lc Diameter of exposed conductive particles Ld Maximum diameter of the recess Le, Lf maximum depth

Claims

1. An anisotropic conductive film having conductive particles disposed in an insulating resin binder, A repeat unit of conductive particles, which is formed by parallel conductive particle rows in which conductive particles are aligned in a line with spaces therebetween, is repeatedly arranged; the repeating units are repeated in both the vertical and horizontal directions when the anisotropic conductive film is viewed in a plan view, When regular triangles are lined up without gaps, the vertices of the regular triangles overlap with the conductive particles that make up the repeating units. one or more regular triangular regions in which no conductive particles are disposed are present between the repeat units that are repeatedly disposed, so that the individual repeat units are present at intervals from each other in the vertical and horizontal directions; An anisotropic conductive film in which the number of conductive particles constituting the central conductive particle row is greater or less than the number of conductive particles constituting the conductive particle rows on either side of the central conductive particle row in a repeat unit of three parallel rows of conductive particles.

2. An anisotropic conductive film having conductive particles disposed in an insulating resin binder, A repeat unit of conductive particles, which is formed by parallel conductive particle rows in which conductive particles are aligned in a line with spaces therebetween, is repeatedly arranged; When regular triangles are lined up without gaps, the vertices of the regular triangles overlap with the conductive particles that make up the repeating units. one or more regular triangular regions in which no conductive particles are disposed are present between the repeating units that are repeatedly disposed, the number of conductive particles in the parallel conductive particle row increases and decreases, and this increase and decrease is repeated to form a repeat unit, and the increase and decrease in the number of conductive particles is a combination of three or more types of numbers, An anisotropic conductive film in which the number of conductive particles constituting the central conductive particle row is greater or less than the number of conductive particles constituting the conductive particle rows on either side of the central conductive particle row in a repeat unit of three parallel rows of conductive particles.

3. 3. The anisotropic conductive film according to claim 1, wherein the repeating units are arranged over the entire surface of the anisotropic conductive film.

4. The number of conductive particles constituting the conductive particle row arranged in parallel in the repeating unit gradually varies. The anisotropic conductive film according to any one of claims 1 to 3.

5. An anisotropic conductive film according to any one of claims 1 to 4, wherein each side of a polygon formed by sequentially connecting the centers of conductive particles that form the outline of the repeating unit is oblique to the longitudinal or transverse direction of the anisotropic conductive film.

6. 5. An anisotropic conductive film according to claim 1, wherein a polygon formed by sequentially connecting the centers of conductive particles that form the outline of the repeating unit has sides parallel to the longitudinal or lateral direction of the anisotropic conductive film.

7. 7. The anisotropic conductive film according to claim 1, wherein in the repeating unit, the rows of conductive particles are parallel to each other.

8. 8. The anisotropic conductive film according to claim 1, wherein a single conductive particle is repeatedly arranged together with the repeating unit.

9. 9. The anisotropic conductive film according to claim 1, wherein in the repeating unit, the closest distance between adjacent conductive particles is at least 0.5 times the average particle diameter of the conductive particles.

10. The anisotropic conductive film according to any one of claims 1 to 9, wherein the conductive particles constituting the repeating unit are arranged in such a way that conductive particles are present at each lattice point of a hexagonal lattice, but conductive particles at certain lattice points are regularly omitted.

11. The anisotropic conductive film according to any one of claims 1 to 10, further comprising an insulating adhesive layer laminated thereon.

12. 12. The anisotropic conductive film according to claim 1, wherein the shortest distance between repeating units in the longitudinal direction or the transverse direction or both directions is longer than the distance between adjacent conductive particles within the repeating unit.

13. A connection structure in which a first electronic component and a second electronic component are anisotropically conductively connected by the anisotropic conductive film according to any one of claims 1 to 12.

14. A method for manufacturing a connection structure between a first electronic component and a second electronic component by thermocompression bonding the first electronic component and the second electronic component via an anisotropic conductive film, wherein the anisotropic conductive film used in the manufacturing method for the connection structure is an anisotropic conductive film described in any one of claims 1 to 12.

Citation Information

Patent Citations

  • The electrical ignition for the propellant chamber of the bullet

    JP1973087700A

  • Anisotropic conductive film

    JP1997320345A

  • Fine-pitch anisotropic conductive adhesive

    JP2002519473A

  • Anisotropic conductive film and its manufacturing method

    JP2009076431A

  • Anisotropic conductive film and connection structure

    JP2016015205A